2020
DOI: 10.1161/jaha.119.015361
|View full text |Cite
|
Sign up to set email alerts
|

Bias and Loss to Follow‐Up in Cardiovascular Randomized Trials: A Systematic Review

Abstract: Background Loss to follow‐up ( LTFU ) is common in randomized controlled trials. However, its potential impact on primary outcomes from cardiovascular randomized controlled trials is not known. Methods and Results We conducted a prospective systematic review ( PROSPERO : CRD 42019121959) for randomized controlled trials published in 8 leading journals over 5 years from January 2014 to Decem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 136 publications
0
4
0
Order By: Relevance
“…Loss to follow-up (LTFU) is a common phenomenon in clinical trials. More than threequarters of cardiovascular clinical trials have participants who are LTFU, and the statistical handling of these data varies widely [25]. In cardiovascular rehabilitation (CR) trials, dropout rates are as high as 39% [26].…”
Section: Care Coordination For Improving Retentionmentioning
confidence: 99%
“…Loss to follow-up (LTFU) is a common phenomenon in clinical trials. More than threequarters of cardiovascular clinical trials have participants who are LTFU, and the statistical handling of these data varies widely [25]. In cardiovascular rehabilitation (CR) trials, dropout rates are as high as 39% [26].…”
Section: Care Coordination For Improving Retentionmentioning
confidence: 99%
“…A systematic review of 117 trials found almost 80% of them showed a loss of follow-ups, and approximately one in six CVOTs may have a change in the primary outcome. 27 Thus, prevention must be prioritised; and authors should report and provide the baseline characteristics of those participants, the extent of follow‐up prior exclusion, and time of dropout and address that implication of those participants when interpreting results. More importantly, Inadequate allocation concealment may drive differential treatment effects (either overestimation or underestimation 28 ) and considered as an independent factor associated with loss of follow-ups, as allocation concealment was inadequate or unclear in more than 50% of the trials.…”
Section: The Design Of Cardiovascular Outcome Trialsmentioning
confidence: 99%
“…1 However, high loss to follow-up (LTFU) rates are pervasive in modern RCTs and many fail to achieve complete follow-up. 2,3 Efforts to improve and standardize the reporting of LTFU have been ongoing for more than 25 years, and include the Consolidated Standards of Reporting Trials (CONSORT) statement, initially published in 1996 and updated in 2010. 4,5 This statement established recommendations for transparent reporting, including a checklist and flow diagram to facilitate accurate interpretation and critical appraisal of trial design and results.…”
mentioning
confidence: 99%
“…Randomized controlled trials (RCTs) are widely accepted as the gold standard for evaluating the safety and efficacy of new interventions or therapeutic applications 1 . However, high loss to follow‐up (LTFU) rates are pervasive in modern RCTs and many fail to achieve complete follow‐up 2,3 . Efforts to improve and standardize the reporting of LTFU have been ongoing for more than 25 years, and include the Consolidated Standards of Reporting Trials (CONSORT) statement, initially published in 1996 and updated in 2010 4,5 .…”
mentioning
confidence: 99%